Laryngeal Leishmaniasis - Bruno Teixeira de Moraes; Francisco de Souza Amorim Filho; José Caporrino Neto; Paulo Saraceni Neto; José Elson Santiago de Melo Júnior (International Archives of Otorhinolaryngology, 2012)
Summary